Banalização da pirataria na sociedade brasileira: percepções, impactos e meios de combate - PINHEIRO, Thiago Santos (2024)
This work seeks to demonstrate the contradiction that plagues society, namely: piracy, which is prohibited, however, exists and can be committed in a banal way. The research seeks to understand, doctrinally, the meaning of piracy and demonstrate that it is not limited to the street vendor with his stall, at the fair, or the person without formal employment reselling some products. To this end, the study goes through social nuances, as well as presenting the means present in our legal system to combat crime.